Higher white-nose syndrome fungal isolate yields from UV-guided wing biopsies compared with skin swabs and optimal culture media - Seidlova, Veronika; Pikula, Jiri; Kolarik, Miroslav; Nováková, Alena; Cmokova, Adela; Ghazaryan, Astghik; Nemcova, Monika; Bednarikova, Sarka; Patra, Sneha; Kokurewicz, Tomasz; Piacek, Vladimir; Zukal, Jan (BMC veterinary research, 2023)
BACKGROUND: North American bat populations have suffered severe declines over the last decade due to the Pseudogymnoascus destructans fungus infection. The skin disease associated with this causative agent, known as white-nose syndrome (WNS), is specific to bats hibernating in temperate regions. As cultured fungal isolates are required for epidemiological and phylogeographical studies, the purpose of the present work was to compare the efficacy and reliability of different culture approaches based on either skin swabs or wing membrane tissue biopsies for obtaining viable fungal isolates of P. destructans. RESULTS: In total, we collected and analysed 69 fungal and 65 bacterial skin swabs and 51 wing membrane tissue biopsies from three bat species in the Czech Republic, Poland and the Republic of Armenia. From these, we obtained 12 viable P. destructans culture isolates. CONCLUSIONS: Our results indicated that the efficacy of cultures based on wing membrane biopsies were significantly higher. Cultivable samples tended to be based on collections from bats with lower body surface temperature and higher counts of UV-visualised lesions. While cultures based on both skin swabs and wing membrane tissue biopsies can be utilised for monitoring and surveillance of P. destructans in bat populations, wing membrane biopsies guided by UV light for skin lesions proved higher efficacy. Interactions between bacteria on the host's skin also appear to play an important role.
Keywords: Chiroptera; Reproducibility of Results; Bats; ultrafialové záření; reprodukovatelnost výsledků; hibernace; Skin Diseases; Fungal culture; Animals; zvířata; Fungal infection; UV lesions; kožní nemoci; Skin; kultivační média; Pseudogymnoascus destructans skin microbiota; Ultraviolet Rays; syndrom; kůže; Syndrome; Hibernation; Culture Media